Heat transfer and flow structure evaluation of a synthetic jet emanating from a planar heat sink - MURRAY, DARINA; PERSOONS, TIM (My University, 2014)
Direct impinging synthetic jets are a proven method for heat transfer enhancement, and have been subject to extensive research. However, despite the vast amount of research into direct synthetic jet impingement, there has been little research investigating the effects of a synthetic jet emanating from a heated surface, this forms the basis of the current research investigation. Both single and multiple orifices are integrated into a planar heat sink forming a synthetic jet, thus allowing the heat transfer enhancement and flow structures to be assessed. The heat transfer analysis highlighted that the multiple orifice synthetic jet resulted in the greatest heat transfer enhancements. The flow structures responsible for this were identified using a combination of flow visualisation, thermal imaging and thermal boundary layer analysis. The flow structure analysis identified that the synthetic jets decreased the thermal boundary layer thickness resulting in a more effective convective heat transfer process. Flow visualisation revealed entrainment of local air adjacent to the heated surface; this occurred from vortex roll-up at the surface of the heat sink and from the highly sheared jet flow. Furthermore, a secondary entrainment was identified which created a surface impingement effect. It is proposed that all three flow features enhance the heat transfer characteristics of the system.
Journal of Physics: Conference Series
PUBLISHED
Keywords: Direct impinging synthetic jets; Direct impinging synthetic jets